Primary screening of insecticidal efficacy of leaves and seeds of Annona muricuta Linn. against mosquito larvae in the laboratory - Sugeng Juwono Mardihusodo Sugeng Juwono Mardihusodo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1992)
Various species of plants are known to contain different active substances showing insecticidal activities and many of them could be utilized as the alternatives of chemical insecticides with long residual actions. •These studies aimed at elucidating the insecticidal actions of leaves and seeds of Annona muricula Linn. against Aedes and Culex mosquito larvae. The leaves, seed cores and seed walls of A. muricuta were prepared as 10% infusion, and after a serial dilutions of the stock ingredient was made, they were tested for their respective insecticidal actions against the larvae of. Ae. aegypti and Cr. quinquefasciatus under laboratory conditions for 24 and 48 hours.Final results analized showed that the leaves and seed cores of A. muricula in the form of infusion were insecticidal against mosquito larvae tested.Key Words: botanical insecticides - Annona muricuta Linn. Aedes aegypti - Culex quinquefasciatus - mosquito control